2022
DOI: 10.3389/fenvs.2021.794866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land-Use Changes on Soil Properties and Carbon Pools in India: A Meta-analysis

Abstract: Land-use changes (LUC), primarily due to deforestation and soil disturbance, are one of the major causes of soil quality degradation and greenhouse gas emissions. Effects of LUC on soil physicochemical properties and changes in soil quality and land use management strategies that can effectively restore soil carbon and microbial biomass levels have been reported from all over the world, but the impact analysis of such practices in the Indian context is limited. In this study, over 1,786 paired datasets (for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 84 publications
4
8
0
1
Order By: Relevance
“…Land-use change affects nearly one-third of the global land area (Winkler et al, 2021), and changes in land area will inevitably have different impacts on different ecological and environmental indicators. In particular, land-use change may negatively affect carbon pools (Padbhushan et al, 2022) and soil erosion (Gong et al, 2022), and it can also cooperate with climate change to promote net primary productivity (Xiao et al, 2019). It is worth mentioning that surface runoff (Daneshi et al, 2020), the spatial pattern of water quality , and landscape complexity (Galpern and Gavin, 2020) have all been shown to be strongly correlated with land-use change.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use change affects nearly one-third of the global land area (Winkler et al, 2021), and changes in land area will inevitably have different impacts on different ecological and environmental indicators. In particular, land-use change may negatively affect carbon pools (Padbhushan et al, 2022) and soil erosion (Gong et al, 2022), and it can also cooperate with climate change to promote net primary productivity (Xiao et al, 2019). It is worth mentioning that surface runoff (Daneshi et al, 2020), the spatial pattern of water quality , and landscape complexity (Galpern and Gavin, 2020) have all been shown to be strongly correlated with land-use change.…”
Section: Introductionmentioning
confidence: 99%
“…Much literature published on LU conducted in the past years reported that changing natural lands to urban areas, agriculture, or bare ground will lead to frequent environmental issues and flooding due to increased runoff and peak discharge. For example, in the hydrology process (Son et al, 2022;Getachew & Manjunatha, 2022), soil quality (Vanacker et al, 2019;Padbhushan et al, 2022) and climate change (Şen, 2020); these variables are essential to the mitigation of water risk…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have assessed the impact of land-use cover change on carbon stocks (Arrouays et al, 2001;Lozano-Garcıá et al, 2017;Padbhushan et al, 2022). However, the error in estimating carbon stocks based on land-use type alone is large.…”
Section: Significance Of Carbon Storagementioning
confidence: 99%